The concentration of selected organophosphorus pesticides associated with PM10 in agricultural ambient air in Iran: Health risk assessment using Monte Carlo simulation - Asma Tabanasl; Amin Mohammadpour; Aboozar Soltani; Mohammad Hoseini; Mohammadali Baghapour (Ecotoxicology and Environmental Safety)
Organophosphate pesticides, widely utilized for pest management globally, are associated with various adverse health effects upon exposure. This study aimed to investigate the presence of organophosphate pesticides in particulate matter (PM10) and evaluate the potential risks to human health using both deterministic and probabilistic approaches in urban and suburban areas of Yasuj City, Iran. A total of 32 air samples were collected during the study period. Active sampling was conducted using a SKC pump with a selective air inlet, and the samples were analyzed via liquid chromatography-mass spectrometry. The results indicated that Diazinon exhibited the highest average concentration among PM10-bound organophosphate pesticides, measuring 4.23 ng/m³ in suburban areas and 2.51 ng/m³ in urban environments. Although no significant overall difference was observed in organophosphate pesticide levels in PM10 between urban and suburban areas, suburban regions generally exhibited higher concentrations, with the exceptions of Parathion and Butachlor. The hazard index (HI) percentiles for children exposed to these pesticides in Yasuj's air were calculated as 0.0047 (5th percentile), 0.0141 (50th percentile), and 0.0291 (95th percentile). For adults, the corresponding values were 0.0016, 0.0050, and 0.0101, respectively. The median carcinogenic risk (CR) values were estimated at 1.40E-9 for children and 2.49E-9 for adults. Notably, the concentration of Diazinon and its interaction with inhalation rates were critical determinants of HI, while Malathion concentration and its interaction with inhalation rates significantly impacted CR for both demographic groups. Our findings suggest that pesticide levels in urban and suburban air are relatively low and pose minimal health risks. However, the study underscores the necessity for ongoing monitoring and increased public awareness regarding pesticide exposure.